Hoxa cluster genes determine the proliferative activity of adult mouse hematopoietic stem and progenitor cells - Lebert-Ghali, Charles-Étienne; Fournier, Marilaine; Kettyle, Laura M.J.; Thompson, Alexander; Sauvageau, Guy; Bijl, Janet J. (American Society of Hematology, 2016)
Determination of defined roles for endogenous homeobox (Hox) genes in adult hematopoietic stem and progenitor cell (HSPC) activity has been hampered by a combination of embryonic defects and functional redundancy. Here we show that conditional homozygous deletion of the Hoxa cluster (Hoxa−/−) results in a marked reduction of adult HSPC activity, both in vitro and in vivo. Specifically, proliferation of Hoxa−/− HSPCs is reduced compared with wild-type (WT) cells in vitro and they are less competitive in vivo. Notably, the loss of Hoxa genes had little impact on HSPC differentiation. Comparative RNA sequencing analyses of Hoxa−/− and WT hematopoietic stem cells (CD150+/CD48−/Lineage−/c-kit+/Sca-1+) identified a large number of differentially expressed genes, three of which (Nr4a3, Col1a1, and Hnf4a) showed >10-fold reduced levels. Engineered overexpression of Hoxa9 in Hoxa−/− HSPCs resulted in partial phenotypic rescue in vivo with associated recovery in expression of a large proportion of deregulated genes. Together, these results provide definitive evidence linking Hoxa gene expression to proliferation of adult HSPCs.